A dye-affinity cryogel membrane for malate dehydrogenase purification from Saccharomyces cerevisiae. Issue 1 (2nd January 2020) - Hamade, Kamar; Göktürk, Ilgım; Bereli, Nilay; Türkmen, Deniz; Elkak, Assem; Denizli, Adil
Abstract: Cibacron blue F3GA functionalized poly(hydroxyethyl methacrylate) cryogel membranes were prepared and applied for a simple purification of malate dehydrogenase (MDH) from crude extract of Saccharomyces cerevisiae . Swelling tests, scanning electron microscopy, surface area measurements and Fourier transform infrared (FTIR) spectroscopy techniques were used for the characterization of dye-affinity cryogel membranes. Following cell homogenization and extraction, MDH was purified using the dye-affinity cryogel membranes at a high yield of 80.5% with 54-fold purification. Maximum MDH adsorption amount was determined to be 267.7 mg/g of membranes at pH 7.4, 25 °C and a flow rate of 1.0 mL/min. Interestingly, the cryogel membranes were used for several purification runs without any significant decrease in MDH adsorption capacity. Sodium dodecyl sulfate polyacrylamide gel electrophoresis was carried out to assess the purity of the eluted MDH. The obtained results highlight the dye-affinity cryogel membranes as powerful dye affinity adsorbents for MDH purification from S. cerevisiae .